The Development Of English Learning Media Through Powtoon To Improve Student's Reading Comprehension At Xi Grade Of Smk Negeri 1 Dayun - Puput Asri Ramadhani; Prih Febtiningsih; Siti Niah (Syntax Literate, 2023)
Reading comprehension is the interaction between readers and the text in order to form a meaning from the text, which is a complex process that involves word knowledge and world knowledge. In addition, reading comprehension is one of the most important reading skills and is required to achieve the overall goals of the reading process. In reading comprehension, the readers’ involves much more than responses to text. Hence, reading comprehension is a complex mental process. stated reading necessitates a connection between learning activities, the learner's experience, and the learner's prior knowledge in order to form the meaning of a text. Reading comprehension is not an innate ability, nor is it an easily facilitated skill that ends when the reader can recognize and say the written symbols. Indeed, it is a complex process that requires mental abilities and potentials, practice and drill, and the application of various thinking, explanation, analysis, critique, and contrasting skills. People can gain a lot of information and knowledge by reading in this globalization era. Reading comprehension seems to be a skill that everyone should develop. Reading comprehension requires three elements to exist: the reader, the text, and the purposeful activity of reading. Furthermore, the process necessitates ongoing practice, development, and refinement, as well as creativity and critical thinking.